Automatic dataset conversion module from gothic database to shapefile format in geographical information system [electronic resource] - Nurul Shima Nordin, 1979-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013